2004
DOI: 10.1016/s0168-6496(03)00245-9
|View full text |Cite
|
Sign up to set email alerts
|

Electron shuttling via humic acids in microbial iron(III) reduction in a freshwater sediment

Abstract: The biological and chemical potential for electron shuttling via humic acids was evaluated by analyzing the depth distribution of humic-acid-reducing and iron-reducing bacteria in a freshwater sediment, and correlating it to the redox characteristics of humic acids and iron. Physicochemical analysis of profundal sediments of Lake Constance revealed a distinct stratification, with oxygen respiration, microbial iron and sulfate reduction, and methanogenesis allocatable to defined layers. Among the acid-extractab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
238
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(248 citation statements)
references
References 36 publications
6
238
3
1
Order By: Relevance
“…Moreover, the 29 N 2 production rate was significantly correlated with the iron(III) reduction rate (P < 0.0001), which further demonstrated the existence of Feammox in DIRB enrichments, leading to more NH 4 + consumption (Figure 3). The previous studies have shown that substrate molecules containing the lighter 14 N atom are typically consumed at higher rates than the heavier 15 N atom due to the isotopic fraction effect. 34−36 The higher concentration of 29 N 2 production than 30 N 2 suggested that preferential conversion of 14 N-NH 4 Cl and 14 N-NO x to N 2 in both the ferrihydrite enrichments.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Moreover, the 29 N 2 production rate was significantly correlated with the iron(III) reduction rate (P < 0.0001), which further demonstrated the existence of Feammox in DIRB enrichments, leading to more NH 4 + consumption (Figure 3). The previous studies have shown that substrate molecules containing the lighter 14 N atom are typically consumed at higher rates than the heavier 15 N atom due to the isotopic fraction effect. 34−36 The higher concentration of 29 N 2 production than 30 N 2 suggested that preferential conversion of 14 N-NH 4 Cl and 14 N-NO x to N 2 in both the ferrihydrite enrichments.…”
Section: ■ Discussionmentioning
confidence: 99%
“…However, most experiments utilizing OM as a terminal electron acceptor have been performed with alkaline extracts: reduced humic acids have been shown to transfer electrons abiotically to terminal electron acceptors, such as metals, thereby functioning as electron shuttles between microbes and electron acceptors (Kappler et al, 2004). Humic acids therefore possess a redox-mediating ability which positively affects the cycling of redox-active minerals, including Fe(III) and Mn(IV) / Mn(III), in conjunction with transformation of organic and inorganic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…NOM was found to greatly enhance the reduction of a key element in soil and sediment such as Fe(III) metals or Fe(III) oxides by a variety of microorganisms (Lovley 1996;Lovley et al 1998;Nevin & Lovley 2000;Royer et al 2002;Chen et al 2003;Kappler et al 2004). Lovley (1996) postulated that humic substances were likely acting as electron mediators or shuttles between microorganisms and Fe(III) or Fe(III)-oxide minerals.…”
Section: Transport and Redox Reactionsmentioning
confidence: 99%